Analyzing of fused deposition modeling nozzle for extruding biomaterials - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar (Politeknik Mukah, 2015)
Rapid prototyping (RP) is one of the advanced technologies which contribute a lot of benefits in manufacturing product. Fused Deposition Modeling (FDM) is one of the RP technologies that have been widely used for fabricating three dimensional products. There has been a lot of improvement and research has been done in terms of hardware and software for providing better and smooth surface finish. The key to have good and quality product lies within the design of the nozzle that capable of extruding the material (filament form). Extruded material is one of the problems that need to be concern as the properties of each material is different. Biomaterial such as poly-ɛ-caprolactone (PCL) is synthetic biomaterial and widely used in orthopedic surgery. This material has been used for fabricating reconstructive structure for bone replacement. Analyzing and development of FDM nozzle is very important for extruding biomaterial effectively. Simulation has been done and the factors that affect the pressure drop along the nozzle are liquefier length, nozzle angle and nozzle diameter. These three factors have been analyzing using computational fluid dynamic method and the pressure drops has been recorded. All the research factor contributes significant effect on varies the road width thus affecting the quality scaffold design.